Pengurangan Akumulasi Plak gigi dengan membandingkan metode mengunyah permen karet xylitol dan berkumur teh hijau - Dedi Sumantri; Fuccy Utami Syafitri (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2013)
Carries and periodontal disease are the biggest problem in dental health which require serious attention. The main cause of carries and periodontal disease is dental plaque. To prevent it, we could control the amount of plaque by combining chemical and mechanical agent. Another well know alternative to control the plaque amount are the use of xylitol and green tea extract. This research aimed to determine reducing dental plaque accumulation by comparative of methods between chewing xylitol bubble gumwith gargling green tea extract.This research using the quasy experiment with 56 samples which devided in two groups where each groups accept a different action. The results showing analysis of data was using paired samples T test and independent samples T test based of 0,05 as significant number. The univariat analysis from each variable showed that there was a significant difference (p<0,05). Bivariat analysis between variable showed that there was no significant difference p > 005 between chewing xylitol bubble gum with gargling greentea extract in reducing dental plaque accumulation. The conclusion from this study was Chewing xylitol bubblegum and gargling green tea extract have the same injluence in reducing dental plaque accumulation.